Pengembangan Media JESIAMAR (Jelajah Situs Mata Air) di Kota Batu untuk Pembelajaran Sejarah Lokal Era 4.0 Berbasis Foto 360° di Kelas X SMA Negeri 02 Batu - Hendika Wicaksana; Najib Jauhari; Wahyu Djoko Sulistyo (Universitas Pancasakti Tegal, 2021)
Efforts to increase knowledge of local history by using digital-based media are very important, so that the objectives of learning local history can be realized properly. The current industrial era 4.0 is known for its extraordinary technological developments, it is time for the development of information technology to be applied in the world of education, especially in learning media. Learning media has a very important position in the learning process, one which is for learning local history. Development of media is carried out using development research methods with ADDIE stages (analysis, design, development, implementation, and evaluation), but in this research at the design stage of the media. Local history is rarely taught and known in the classroom, this can be seen when distributing questionnaires to 150 students at SMA Negeri 02 Batu resulting in 70,9% of students rarely understanding the potential of local history and 13,2% students not understanding at all. In addition, based on the questionnaire that has been distributed, 72.2% students are interested in the media that is used to facilitate the learning of local history based on 360° photos, especially the material on historic springs in Batu City.